2005
DOI: 10.1136/bjo.2004.053561
|View full text |Cite
|
Sign up to set email alerts
|

Visual loss following removal of intraocular silicone oil

Abstract: Aim: To investigate the cause of visual loss following removal of intraocular silicone oil in patients who underwent vitrectomies for retinal detachment or giant retinal tear. Methods: The clinical records of three cases with visual loss following removal of silicone oil were reviewed. Investigations carried out included fundus fluorescein angiogram, optical coherence tomography, and electrophysiological studies. Results: Visual acuities dropped from 6/9 to 6/36 in two cases and 6/24 to 3/24 in the third. None… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 9 publications
2
82
1
10
Order By: Relevance
“…In all of our cases good vision was documented following initial vitrectomy and silicone oil exchange and vision fell immediately after oil removal. The timing of visual loss is similar to most previous reports 12,16,17 although it is notable that Cazabon et al 20 reported visual loss 1 week following oil removal. Whether visual loss with silicone oil in situ is an entirely different Eye phenomenon from visual loss after oil removal is yet to be established.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In all of our cases good vision was documented following initial vitrectomy and silicone oil exchange and vision fell immediately after oil removal. The timing of visual loss is similar to most previous reports 12,16,17 although it is notable that Cazabon et al 20 reported visual loss 1 week following oil removal. Whether visual loss with silicone oil in situ is an entirely different Eye phenomenon from visual loss after oil removal is yet to be established.…”
Section: Discussionsupporting
confidence: 73%
“…Several hypotheses have been proposed including sudden changes in potassium concentration in retro-oil fluid that may lead to macular dysfunction due to photoreceptor apoptosis on oil removal, 18,20 photo-toxicity at the time of silicone oil removal, 15,21,22 and fibrogenic growth factor disturbances. 23 Of the 14 patients who had at least two SL reduction in visual acuity in our study this appeared to happen at the time of oil removal.…”
Section: Discussionmentioning
confidence: 99%
“…Cazabon et al also reported the use of mfERG in evaluating unexplained visual loss after silicone oil removal in three patients who had vitrectomies for retinal detachment. 25 mfERG demonstrated reduced response at the central macula which correlated with the reduction in pattern electroretinogram amplitude, suggestive of macular dysfunction. The exact mechanism of visual loss however remained uncertain.…”
Section: Retinal Surgery Macular Hole and Epiretinal Membranementioning
confidence: 99%
“…Serum Ocular fluid-to-serum ratio SO patients (n = 16) Controls (n = 27) SO patients (n = 16) Controls (n = 27) SO patients (n = 16) Controls (n = 27) retinal toxicity is thought to be fundamental to this visual loss (Winter et al 2000;Newsom et al 2004;Cazabon et al 2005;Herbert et al 2005;Williams et al 2008;Michel et al 2009;Scheerlinck et al 2015). This study investigated the vitreous concentration of K + during SO endotamponade and its potential association with the development of SORVL.…”
Section: Ocular Fluidmentioning
confidence: 99%
“…Although considered to be safe, well tolerated, and not affecting retinal physiology, up to a third of patients treated by SO tamponade for retinal detachments without macular involvement may suffer from SO-related visual loss (SORVL) (Newsom et al 2004;Cazabon et al 2005;Herbert et al 2005;Williams et al 2008;Michel et al 2009;Christensen & la Cour 2012;Scheerlinck et al 2015). This irreversible, profound and unexplained visual loss can occur during SO tamponade or immediate after SO removal and cannot be explained by complications such as cystoid macular oedema, hyper-or hypotony, or epiretinal membranes (Newsom et al 2004;Cazabon et al 2005;Herbert et al 2005;Williams et al 2008;Michel et al 2009;Christensen & la Cour 2012;Scheerlinck et al 2015). Evaluation by visual field tests or microperimetry typically reveals a small deep central scotoma and a severely decreased central macular function can be detected by multifocal electroretinography (Newsom et al 2004;Herbert et al 2005;Scheerlinck et al 2015).…”
Section: Introductionmentioning
confidence: 99%